2018
DOI: 10.1002/jcp.26386
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells rescue cardiomyopathy induced by P. gingivalis‐LPS via miR‐181b

Abstract: Systemic inflammation induced by bacterial infection is one of several causative agents for cardiovascular disorders in patients with periodontal disease. Experimental results indicate that miRNAs play important roles in systemic inflammation induced by endotoxins. Further evidence states that stem cell based therapy shows potential in the treatment of inflammatory responses induced by sepsis. This study investigates if stem cells show protective effects on cardiomyocyte damage induced by porphyromonas gingiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Periodontitis (PD) is a bacterial infection in the tissue that supports the teeth, leading to chronic local inflammation, destruction of connective tissue and alveolar bone, and eventually loss of teeth. It is also associated with an increase of myocardial cell damage and heart failure [ 1 , 2 ]. Porphyromonas gingivalis (PG) is a gram-negative bacterial pathogen often identified in adult PD, and systemic exposure to pro-inflammatory factors from PG, including lipopolysaccharide, may contribute to CVD [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis (PD) is a bacterial infection in the tissue that supports the teeth, leading to chronic local inflammation, destruction of connective tissue and alveolar bone, and eventually loss of teeth. It is also associated with an increase of myocardial cell damage and heart failure [ 1 , 2 ]. Porphyromonas gingivalis (PG) is a gram-negative bacterial pathogen often identified in adult PD, and systemic exposure to pro-inflammatory factors from PG, including lipopolysaccharide, may contribute to CVD [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a paper published by Lee et al (2006), it was evidenced that Porphyromonas gingivalis impairs cardiomyoblasts H9c2 through the promotion of hypertrophy factors and stimulation of the MMP9 fibrosis molecule. A previous work demonstrated that cardiomyopathy stimulated by Porphyromonas gingivalis in part includes p38 MAPK induction [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted using a Direct-zol™ RNA MiniPrep commercial kit (Zymo Research Corporation, CA, USA) according to the manufacturer’s protocol [ 65 , 66 ]. miRNAs were reverse transcribed to cDNA using a miRNA cDNA synthesis kit (Takara, Shiga, Japan) as described previously [ 16 , 67 ]. hsa-miR-4535 and Smad4 expression was detected by real-time PCR in a LightCycler 96 Systems (Roche, Basel, Switzerland) using the standard LightCycler 480 SYBR Green I Master protocol.…”
Section: Methodsmentioning
confidence: 99%